175k views
4 votes
H(n) = n^2 - 4n; Find h(-3)

2 Answers

1 vote

Answer:

h(-3)= (-3)^2 - 4(-3)

9+12= 21

User Kjara
by
4.8k points
1 vote

For this case we have the following function:


h (n) = n ^ 2-4n

We must find the value of the function when
n = -3.

Substituting we have:


h (-3) = (- 3) ^ 2-4 (-3)

We must bear in mind that the law of multiplication signs complies:


- * - = +

So:


h (-3) = 9 + 12\\h (-3) = 21

Answer:


h (-3) = 21

User Mingjiang Shi
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.